ANALISIS PREFERENSI MASYARAKAT TERHADAP MAQASID SYARIAH ISLAMIYAH YANG DITERAPKAN PADA RUMAH SAKIT ISLAM DI SURABAYA - Faid Arinal Firdaus; Muhamad Nafik H. R. (Universitas Airlangga, 2018)
Sharia Hospital is a hospital whose activities are based on Maqasid Syariah Islamiyah, which includes protection of faith, protection of life, protection of reason, protecton of posterity, and protection of property. Sharia-based services are considered very important considering the majority of Indonesian citizen are Muslims. The existing Islamic hospital in Indonesia which has a certificate of sharia label is currently only 2 (two) Islamic hospitals from about 300 Islamic hospitals that are in the auspices of the Islamic Health Assembly All of Indonesia (MUKISI). This study aims to determine the level of preference or the tendency of the community to sharia-based hospital services. This research uses quantitative approach with quantitative descriptive method by describing or explaining data from each of the collected variables. The result of the research based on data analysis shows that the awareness of the importance of Maqasid Syariah Islamiyah in Islamic hospital service is quite high, The results based on data analysis show that awareness of the importance of Maqasid Syariah Islamiyah in Islamic hospital services is very high. From result of calculation of multiple regression showed variable (X) Maqasid Syariah Islamiyah significant to variable (Y) interest and preference of patient in choosing hospital. REFERENCESAl Qur’an dan Terjemahannya: Departemen Agama RI, 2000, Diponegoro, BandungAbidin, Said Zainal. 2008. Strategi Kebijakan dalam Pembangunan dan Ekonomi Politik. Jakarta: Suara BebasAbubakar, Triyantini, R. Sunarlim, H. Setiyanto & Nurcahyadi. 2001. Pengaruh Suhu dan Waktu Pasteurisasi Terhadap Mutu Susu Selama Penyimpanan. Jurnal Ilmu Ternak dan Veteriner 6(1): 45–50.Arif, Abubakar dan Wibowo. 2008. Akuntansi Keuangan Dasar 2. Jakarta : Pt. GrasindoArikunto, S. 1998. Prosedur Penelitian Suatu Pendekatan Praktek. Jakarta: Rineka CiptaArnalia, Euis & M. Nur Riyanto Al Arif. 2010. Teori Mikro Ekonomi Suatu Perbandingan Ekonomi Ilam dan Ekonomi Konvensional. Jakarta: KencanaAzwa, Saifudin. 2003, Penyusunan Skala Psikologi. Yogyakarta: Pustaka pelajar.Brockopp, Dorthy. Y dan Toisma, Marie T. H. 1999. Dasar-dasar Riset. Keperawatan Edisi 2. Jakarta: EGCEriyanto. (2002). Analisis Framing. Yogyakarta: LkiSGhozali, Imam. 2006. Aplikasi Analisis Multivariate dengan Program SPSS. (Edisi Ke 4). Semarang: Badan Penerbit Universitas Diponegoro.Hasan, M. Iqbal. 2002. Pokok-pokok Materi Metodologi Penelitian dan Aplikasinya. Bogor: Ghalia. Hasan, M. Iqbal. 2005. Pokok – Pokok Materi Statistik 2. Jakarta: PT. Bumi AksaraIndarto. 2011. Analisis Faktor-Faktor Yang Mempengaruhi Penghentian. Prematur Atas Prosedur Audit. Jurnal Dinamika Sosial Ekonomi Volume. 7 Nomor 2.Istijanto. 2005. Riset Sumber Daya Manusia. Jakarta: PT. Gramedia. Pustaka UtamaJauhar, Ahmad Al-Mursi Husain. 2010. Maqashid Syari’ah, alih bahasa Khikmawati. Jakarta: AmzahKhallaf, Abdul Wahhab. 1994. Ilmu Ushul Fiqh, alih bahasa M.Zuhri dan Ahmad Qarib, Semarang: Dina Utama Semarang (Toha Putera Group).Kotler, Philip. 2000. Manajemen Pemasaran. Jakarta: PT. PrenhallindoLamsudin, Rusdi. 2002. Strategi Stroke Indonesia. Jakarta: Kompas 17 SeptemberLichtenstein, S & P. Slovic. 2006. The Construction of Preference. New York: Cambridge University Press.Mahfudz, Sahal. 2011. Nuansa Fiqih Sosial. Yogyakarta : LKiS Muhammad Syarif Chaundry, 2012. Sistem Ekonomi Islam Prinsip Dasar. Jakarta: Kencana Prenada Media GroubMuchtarom, Malichah. 1986. Peranan Rumah Sakit Islam dalam Menyongsong Kesehatan Bagi Semua di Tahun 2000. Jakarta: Penerbit RajawaliMuflih, Muhammad. 2006. Perilaku Konsumen dalam Perspektif Ilmu Ekonomi Islam. Jakarta: PT Raja Grafindo PersadaMoleong, Lexy J. 2007. Metodologi Penelitian Kualitatif. Bandung: PT. Remaja Rosda KaryaPradja, Juhaya S. 1998. Filsafat Hukum Islam. Bandung: Yayasan Pengembangan dan HumanioraRitonga, M. Jamiluddin Ritonga. 2004. Riset Kehumasan. Jakarta: Grasindo.Saebani, Beni Ahmad. 2008. Metode Penelitian Hukum. Bandung: Pustaka Setia. Hadikusuma.Said, Syihabudin & Ma’zumi, M. 2008. Falsafah dan Perilaku Ekonomi Islam. Jakarta: Diadit MediaSchiffman, Leon, & Kanuk, Leslie Lazar. 2008. Consumer Behaviour 7th Edition (Perilaku Konsumen). Jakarta: PT. Indeks.Sudijono, Anas. 2012. Pengantar Statistik Pendidikan. Jakarta: PT. Raja Grafindo PersadaSuliyanto. 2011. Ekonometrika Terapan: Teori dan Aplikasi dengan SPSS. Yogyakarta: AndiSupriyadi. 2010. Teknologi Pembelajaan Fisika. Yogyakarta: FMIP